Longitudinal Changes in Trauma Narratives over the First Year and Associations with Coping and Mental Health - Booker, Jordan A. (J Affect Disord, 2020)
BACKGROUND: The structure of trauma memories impacts mental health, but questions remain about how structure changes with time and may shape coping with trauma. This study considered the structure of trauma narratives collected during an emergency department (ED) visit and at one-year follow-up. We addressed change in narrative structure over time, the extent structure predicted twelve-month psychological symptoms, and possible mechanisms in coping responses. METHODS: Sixty-eight community adults (age range 18–67; 41% women) recruited from a trauma center ED provided narratives of the traumatic event that brought them to the ED. Participants provided multiple follow-up reports on psychological symptoms and coping strategies, and another narrative of the traumatic event at twelve months. RESULTS: Narrative structure improved over time. Baseline narrative structure was negatively associated with twelve-month depressive and posttraumatic symptoms. Two measures of trauma narrative structure—interpretive elaboration and coherence—predicted change in coping strategies. Interpretive elaboration (rich details of the subjective experience) promoted early gains in endorsed engagement and later declines in endorsed disengagement. Coherence (the overall thematic structure of the narrative) buffered participant endorsement of disengagement at earlier follow-ups. Engagement was tied with fewer reported symptoms, whereas disengagement was associated with higher reported symptoms. Coping served as a mediator between baseline narrative structure and later mental health. LIMITATIONS: The study sample was relatively small and depended on self-reports for symptoms. Conclusions: Findings suggest there is meaningful variability in trauma memory structure, and early recollections of traumatic experiences may improve targeting of individuals in need of active interventions.